Faktor Yang Berhubungan Dengan Keikutsertaan Ibu Hamil Dalam Kelas Ibu Hamil - Desmariyenti Desmariyenti; Susi Hartati (LPPM Universitas Muhammadiyah Riau, 2019)
Abstract Pregnant women class is a learning facility for pregnant women in undergoing the process of pregnancy and postpartum. Based on the preliminary survey conducted by researchers in the work area of ​​Payung Sekaki Primary Health Center, it was obtained data that the narration of midwives working in the work area of ​Payung Sekaki Primary Health Center was indeed carried out, but there were still many pregnant women who had not utilized maternal facilities optimally. The purpose of this study is the Factors Associated with the Participation of Pregnant Women in the Work Area Payung Sekaki Primary Health Center 2018. This type of research is quantitative using correlation analysis with Chi-square. The population in the study amounted to 297 people, with a total sample of 75 people with accidental sampling technique. This research was carried out in the work area of ​​Payung Sekaki Primary Health Center Pekanbaru on 05 to 28 July 2018. The results showed that there was a relationship between knowledge and maternal participation in the class of pregnant women in the work area of Payung Sekaki Primary Health Center with a p-value = 0,000, there was a relationship between parity with the participation of pregnant women in the Working Area of ​​Payung Sekaki Primary Health Center with a p-value = 0.025 and there is a relationship of family support with the participation of pregnant women in the work area of Payung Sekaki Primary Health Center with a p-value = 0.03 with a degree of Error α = 0,1. Keywords : Knowledge, parity, family support, participation of pregnant women Bibliography : 15 References (2007-2018).